Removal of nitrate and phosphate from municipal wastewater sludge by Chlorella Vulgaris, Spirulina Platensis and Scenedesmus Quadricauda - Khan Chowdhury, Ahmed Jalal; Alam, Md. Zahangir; W.A., Matin; Yunus, Kamaruzzaman; John, Akbar; Hossain, Toffazel (IIUM Press, 2011)
Nitrate and phosphorus in wastewater contribute to health and environmental threats as they are linked to illnesses as well as ecosystem disruption via algal blooms in contaminated water bodies. Based on above perspectives a comparative study was conducted on three local freshwater microalgae:Chlorella vulgaris, Spirulina platensis and Scenedesmus quadricauda to evaluate their effects on nitrate and phosphorus removal from municipal wastewater sludge (MWS). Algae performance in removing nitrate and phosphorus was evaluated by measuring nitrate and phosphorus content of MWS incubated with the strains for 7 days. Instantaneous readings were taken every 48 hours to determine periodic levels of the nutrients phosphate and nitrate. BOD5 was also evaluated to identify the strain with the most robust growth that would demand for oxygen the most in the dark. Spirulina platensis was shown as the most efficient microalgae to reduce nitrate in MWS and the best-growing among the three strains, while Chlorella vulgaris removed phosphorus the most effectively. Thus Spirulina and Chlorella could be potential candidates by showing their intrinsic merit for the reduction of phosphate and nitrate in wastewater treatment.